2020
DOI: 10.1101/2020.04.13.039362
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

PLK1- and PLK4-mediated asymmetric mitotic centrosome size and positioning in the early zebrafish embryo

Abstract: Factors that regulate mitotic spindle positioning have been elucidated in vitro, however it remains unclear how a spindle is placed within the confines of extremely large cells. Our studies identified a uniquely large centrosome structure in the early zebrafish embryo (246.44±11.93μm 2 mitotic centrosome in a 126.86±0.35μm diameter cell), whereas C. elegans centrosomes are notably smaller (6.75±0.28μm 2 mitotic centrosome in a 55.83±1.04μm diameter cell). During early embryonic cell divisions, cell size change… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…This coincides with a clear g-tubulin accumulation on either side of the nucleus. We and others have observed that PCM1, centrin and g-tubulin form cytoplasmic accumulations that appear as a large clouds on either side of the nucleus during the first cell divisions of the zebrafish embryo (Dekens et al, 2003;Lindeman and Pelegri, 2012;Rathbun et al, 2020;Stowe et al, 2012). Why these structures that function as MTOCs are so large is not clear, but might have to do with the large size of the embryo (see also below).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…This coincides with a clear g-tubulin accumulation on either side of the nucleus. We and others have observed that PCM1, centrin and g-tubulin form cytoplasmic accumulations that appear as a large clouds on either side of the nucleus during the first cell divisions of the zebrafish embryo (Dekens et al, 2003;Lindeman and Pelegri, 2012;Rathbun et al, 2020;Stowe et al, 2012). Why these structures that function as MTOCs are so large is not clear, but might have to do with the large size of the embryo (see also below).…”
Section: Discussionmentioning
confidence: 95%
“…As the MS data revealed a possible interaction between Cfap53 with PCM1 and g-tubulin, we investigated the localization of these and other centrosomal proteins in wild type and MPcfap53-/-embryos. In wild type embryos, g-tubulin, PCM1 and Centrin were localized in the large MTOC structures typical for early cleavage stage zebrafish embryos ( Fig 5A-C) (Dekens et al, 2003;Lindeman and Pelegri, 2012;Rathbun et al, 2020). In arrested MPcfap53-/-embryos, g-tubulin signal was present, albeit at reduced levels, and it formed granule-like foci dispersed throughout the cytoplasm (Fig.…”
Section: Cfap53 Facilitates the Formation Of The Mtoc After Fertilizamentioning
confidence: 85%
See 2 more Smart Citations
“…Coverslips were rinsed with diH2O and mounted on glass slides using ProLong Gold mounting media (Thermo Fisher Scientific; P36934). Zebrafish embryos were fixed using 4% PFA at 4C overnight, for immunostaining see [24,25]. See Key Resources Table for list of antibodies used in this study.…”
Section: Immunofluorescencementioning
confidence: 99%